Nilai Nutrisi Pakan dan Respons Pertumbuhan Ikan Louhan (Amphilopus trimaculatus) Yang Diberi Tepung Bungkil Kelapa Sawit Fermentasi Dengan Lama Waktu Berbeda - Asmara, Byu Aji Putra; Sukarti, Komsanah; Ma’ruf, Mohamad; Kusdianto, Heru (Jurnal Akuakultur Sungai dan Danau, 2024)
Amphilopus trimaculatus (Louhan in Indonesia) is a freshwater ornamental fish that is famous among the public because it is believed to bring good luck to its owner, so it has a fairly high selling price. Keeping flowerhorn fish requires food so that the fish can grow well. This research aims to analyze the nutritional value of artificial feed made from palm kernel meal which is fermented using EM4 for different lengths of time and to analyze its effect on the growth and feed conversion ratio of flowerhorn fish. This research used a Completely Randomized Design (CRD) with 4 treatments and 3 replications. The treatments applied were P1 not fermented, P2 fermented for 3 days, P3 fermented for 5 days and P4 fermented for 7 days. The fish used in this study had an initial length of 3-5 cm and an initial weight of 1.5-2 g. Fish were kept for 40 days in aquariums measuring 30×30×40 cm using a recirculation system. Each aquarium is filled with 20 liters of water with a stocking density of 10 fish/aquarium. Fish were fed 3 times a day using ad-satiation. The results of the proximate nutritional analysis of the feed showed that the protein content of the feed was 32.53%, 35.97%, 37.31% and 36.31% for P1, P2, P3 and P4 respectively. The feed fat content was 6.19%, 7.26%, 6.38% and 7.44% for P1, P2, P3 and P4 respectively. Data analysis was carried out using analysis of variance (ANOVA) with a confidence level of 95% and continued with the Duncan Multiple Range Test (DMRT). The best fish growth performance and feed conversion ratio were achieved by P2, although statistically there was no significant difference in fish growth (P<0.05) but had a significant effect on the feed conversion ratio (P>0.05).